PENERAPAN FATWA DEWAN SYARIAH NASIONAL TENTANG HUKUM JAMINAN DALAM AKAD PEMBIAYAAN MUDHARABAH - Rd Nurhayati; Muhammad Saleh; Abdullah Sani Kurniadinata (Prodi Hukum Ekonomi Syariah (Muamalah), 2018)
In classical fiqh study, akad Mudharabah is a contract that is based on the elementof Trust (trust) so that in the application of financing mudharabah not necessary collateralor guarantees. Along with the development of the Times and the human character inrunning the business, there is a thought of thinking so that it is necessary to ijtihad new toa problem one of them Akad Mudharabah. The purpose of this research is to determine theprovisions of the guarantee in the distribution of Mudharabah financing in non-bankfinancial institutions, the guarantee in the fatwa DSN on Mudharabah financing, and theapplication of the fatwa DSN about the assurance in the Mudharabah financing contractThis study uses a qualitative descriptive approach, conducted by collecting data and thendescribing the observation of interviews and documentation. From the results of thisresearch can be concluded that the application of the fatwa of the National Sharia Board(DSN) about the guarantee in this Mudharabah financing is based on the attitude of societytoday that often do social irregularities (moral hazard), especially in Mudharabah financingthat does not have a very high risk. The function of the guarantee is not intended formendzolimi intention but as a control of the possibility of deviations by mudharib, therefore,the DSN issued a fatwa that must be obeyed by Sharia financial institutions one of the BMT Al-Amanah Ciawi Tasikmalaya based on the fatwa DSN No: 07/DSN-MUI/IV/2000 onMudharbah financing